Effectiveness of interventions targeting antibiotic use in long-term aged care facilities: a systematic review and meta-analysis - Ling Li; Johanna I Westbrook; Melissa T Baysari; Magdalena Z Raban; Claudia Gasparini (BMJ Open)
Objectives There are high levels of inappropriate antibiotic use in long-term care facilities (LTCFs). Our objective was to examine evidence of the effectiveness of interventions designed to reduce antibiotic use and/or inappropriate use in LTCFs.Design Systematic review and meta-analysis.Data sources MEDLINE, Embase and CINAHL from 1997 until November 2018.Eligibility criteria Controlled and uncontrolled studies in LTCFs measuring intervention effects on rates of overall antibiotic use and/or appropriateness of use were included. Secondary outcomes were intervention implementation barriers from process evaluations.Data extraction and synthesis Two reviewers independently applied the Cochrane Effective Practice and Organisation of Care group’s resources to classify interventions and assess risk of bias. Meta-analyses used random effects models to pool results.Results Of include studies (n=19), 10 had a control group and 17 had a high risk of bias. All interventions had multiple components. Eight studies (with high risk of bias) showed positive impacts on outcomes and included one of the following interventions: audit and feedback, introduction of care pathways or an infectious disease team. Meta-analyses on change in the percentage of residents on antibiotics (pooled relative risk (RR) (three studies, 6862 residents): 0.85, 95% CI: 0.61 to 1.18), appropriateness of decision to treat with antibiotics (pooled RR (three studies, 993 antibiotic orders): 1.10, 95% CI: 0.64 to 1.91) and appropriateness of antibiotic selection for respiratory tract infections (pooled RR (three studies, 292 orders): 1.15, 95% CI: 0.95 to 1.40), showed no significant intervention effects. However, meta-analyses only included results from intervention groups since most studies lacked a control group. Insufficient data prevented meta-analysis on other outcomes. Process evaluations (n=7) noted poor intervention adoption, low physician engagement and high staff turnover as barriers.Conclusions There is insufficient evidence that interventions employed to date are effective at improving antibiotic use in LTCFs. Future studies should use rigorous study designs and tailor intervention implementation to the setting.